2020
DOI: 10.53491/porosonim.v1i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Praktik Dialog Antar Umat Beragama

Abstract: The harmony of religious people is a manifestation of one of the ideals of Indonesian nation that stood on the differences, including religious differences. This article aims to analyse the practice of religious harmony between Islam and Christian in the Minang realm. The object analyzed is the community of Muslim and Christian in Lima Puluh Kota Regency, West Sumatera. Lima Puluh Kota Regency was chosen based on facts other than the Muslim majority, and also the region that still retains the Minangkabau custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Considering that this action dialogue is more effective, it differs significantly from several studies on interfaith dialogues that have taken place. For example, a study by Zilal Afwa Ajidin found that interfaith dialogues are still conventional and tend to be non-formal dialogues that occur in daily life (Ajidin, 2020). The research by Halim & Jambi (2015) focuses on the outcomes of interfaith dialogue when people reach adulthood.…”
Section: The Implications Of Implementing Ctrs Program By Eco Bhinnek...mentioning
confidence: 99%
“…Considering that this action dialogue is more effective, it differs significantly from several studies on interfaith dialogues that have taken place. For example, a study by Zilal Afwa Ajidin found that interfaith dialogues are still conventional and tend to be non-formal dialogues that occur in daily life (Ajidin, 2020). The research by Halim & Jambi (2015) focuses on the outcomes of interfaith dialogue when people reach adulthood.…”
Section: The Implications Of Implementing Ctrs Program By Eco Bhinnek...mentioning
confidence: 99%
“…Hal ini mengindikasikan bahwa toleransi berada pada ranah sosial, sementara ranah budaya, kelompok agama minoritas masih terus menyesuaikan dengan kepentingan kelompok mayoritas. Pembatasan ini mungkin muncul karena keyakinan kedua kelompok agama bahwa agama yang diyakini merupakan jalan keselamatan paling benar (Ajidin, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Meanwhile, Christian figures argue that in Christianity, the concept of love is a bridge for inter-religious dialogue to maintain harmony between religious communities. As minorities, Christian religious figures feel the pressure of being a minority, but still receive general protection when carrying out worship according to their religion (Abidin, 2020).…”
Section: Everything Stated In Thementioning
confidence: 99%